THE EFFECT OF DIGITAL MEDIA IN THE FORM OF QUIZLET ON STUDENTS’ BASIC ENGLISH LITERACY TO NINTH-GRADE STUDENTS IN SMP NEGERI 3 ABIANSEMAL - Widnyani, Ni Kadek; Padmadewi, Ni Nyoman; Dewi, Kadek Sintya (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This study investigates the impact of Quizlet's implementation on students’ basic English literacy skills in ninth-grade students of SMP Negeri 3 Abiansemal in the academic year 2024/2025. It uses a quantitative method with a quasi-experimental post-test-only control group design. Cluster random sampling was applied to this study, with 58 students from two ninth-grade classes divided into experimental and control groups. The experimental group was given a treatment with Quizlet in while activity, while the control group used conventional media. At the end of the treatment, both groups were given the post-test. The data was analyzed using an Independent sample t-test. The finding showed that there was a significant effect of Quizlet on students’ basic English literacy in ninth-grade students of SMPN 3 Abiansemal. Students who learn using Quizlet get higher post-test scores than those who use conventional media (Sig. (2-tailed (0.000) < 0.05). In addition, Cohen’s effect was 1.531, which falls into large effect. This concludes that implementing Digital Media in the form of Quizlet can influence students’ basic English literacy. Keywords: Digital Media, Quizlet, English Literacy, Basic English Literacy Skills.